Financial Performance of Islamic Commercial Banks Before and During the Covid-19 Pandemic in Indonesia - Wahyu Wastuti; Asyari Hasan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The covid-19 pandemic has dropped the economy of the world. Islamic banks as part of the economy are also affected by this pandemic. The study aims to provide an overview of the performance of Islamic Commercial Banks (BUS) in Indonesia before and during the Covid-19 pandemic. The measurement of financial performance will use several financial ratios, namely ROA, CAR, NPF, FDR, BOPO, and NOM. The research sample is all BUS in Indonesia. The years 2018 and 2019 will be used as the period before the Covid-19 pandemic, while 2020 and 2021 will be used as the period during the Covid-19 pandemic. It uses a quantitative method with measurement tools: independent sample t-test and multiple linear regression. The results of the independent sample t-test are the CAR, FDR, and BOPO variables have differences in the period before the pandemic and during the pandemic. While the ROA, NPF, and NOM variables have no difference in the period before and during the pandemic. From the partial multiple linear regression test (t-test), financial ratios in the form of BOPO and NOM influence ROA. While the variables CAR, FDR, and NPF do not affect ROA. On the other hand, simultaneously the variables CAR, NPF, FDR, BOPO, and NOM affect ROA. The research results from this article can be used as a source of information by stakeholders in making policies for a better BUS future.